Exploring OHS trainers’ role in the transfer of training - Freitas, A. C.; Silva, S. A. (Safety Science, 2017)
Safety training (ST) is essential for workplace safety and to be effective requires that the learned knowledge and skills are transferred to the job. Research on transfer mechanisms and its predictors has neglected trainers’ influence, despite their privileged position on decisions related with training. This study is aimed at identifying: (1) trainers’ perspectives on best practices for enhancing ST success; (2) unexplored transfer factors based on reported best practices; and (3) the trainers’ sense of self-efficacy and personal responsibility regarding ST results. Twenty semi-structured interviews were conducted with experienced and first-line safety trainers, all OHS professionals. Content analysis revealed that trainers attribute training success to factors related to trainees’ individual characteristics, workplace environment and mainly to training design and delivery. OHS professionals’ presence in the workplace emerged as a critical transference trigger suggesting future research to explore under what conditions that effect occurs. Participants reported feeling responsible for training results but revealed a low sense of control. These results confirm that trainers decide on training design and deliver but their role should be expanded so to support training application in the work context. For that purpose, companies must empower safety trainers for enhancing their control over the transfer process.